Stone Island - Griffiths, Nick.; Foxton, Simon; &Son (Firm) (Cinisello Balsamo, Milano : Silvana, 2012)
Published as a companion book to the recent Stone Island 30 exhibition held in Florence, this book is a magnificent pictorial history of the brand's first 30 years. Billed as 'A Photographed Edit of the Stone Island archive', the book is a superb collection of pieces drawn from the archives covering fabric composition -- effectively a giant historical 'Look Book'. Stone Island, designed by Italian designer Massimo Osti in 1982 and currently led by Carlo Rivetti, is known for innovative sportwear with performance fabrics and high technology. 307 photographs of models from the eighties to the present day include sweatshirts, sweaters, trousers and jackets.
Italian, English, and French.
"Printed on the occasion of Stone Island 30 years"--T.p. verso.
Includes introduction by Carlo Rivetti and an essay by Francesco Morace.
boek
Keywords: Stone Island (Firm)